Incidence of Thyroid Diseases in Local Population - Rahman Javed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Thyroid diseases are considered most significant public health dilemma worldwide with global prevalence of 5%-10%. In Pakistan, the hypothyroidism and hyperthyroidism prevalence is 4.1% and 5.1%, respectively. Thyroid disorder is a common, identifiable and simply curable, but if not diagnosed or left untreated can have intense adverse effects. Aim: To evaluate the incidence of thyroid diseases in local population of Lahore. Study design: Cross-sectional study. Methods: It is carried out among patients visiting Arif Memorial Teaching Hospital, Lahore. A total of 257 patients aged between 18 to 65 years with clinical features suggestive of thyroid disorders from October 2021 to November 2022 were included. Patients data were collected through questionnaire and analyzed using SPSS version 25.0. Results: Among 257 respondents, 64.2% were females and the mean age was 41.93±11.522 years. 33.9% respondents had family history of thyroid, 23.8% diagnosed with hypothyroidism, 12.8% with hyperthyroidism and 35.4% with subclinical hypothyroidism while 28% respondents were euthyroid. The association between thyroid disease and age was found statistically significant (P=0.000) but insignificant (P=0.351) between thyroid disease and gender. Conclusion: Study concluded that incidence of thyroid diseases was 72% in study population. Keywords: Incidence, thyroid disease, hypothyroidism, hyperthyroidism, euthyroidism.